2021
DOI: 10.1111/rda.14015
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for increasing the utilization of cattle embryo transfer by small‐scale milk and meat producers in tropical regions

Abstract: Contents Small community cattle farmers in the tropics are facing challenges to deliver quality products whilst under pressure to increase milk and beef yields per cow. These challenges could be partially met by crossbreeding Bos taurus with Bos indicus (F1) cattle utilizing embryo transfer (ET) technology. The Bos taurus infusion would increase milk production, whilst the Bos indicus influence can improve resistance to the harsh environment of the tropics. Here, individuals from existing herds can be used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…The application of the ex situ program for the conservation of oocytes, spermatozoa, and embryos has a significant advantage, allowing their development to be resumed at the desired time [ 23 , 24 ]. Contreras, Galina, and Chenoweth [ 25 ] reported that cryoconservation has a low-efficiency due to the high risk of damaging reproductive materials. For this reason, our initial research mainly focused on the production of embryos and birth rates.…”
Section: Discussionmentioning
confidence: 99%
“…The application of the ex situ program for the conservation of oocytes, spermatozoa, and embryos has a significant advantage, allowing their development to be resumed at the desired time [ 23 , 24 ]. Contreras, Galina, and Chenoweth [ 25 ] reported that cryoconservation has a low-efficiency due to the high risk of damaging reproductive materials. For this reason, our initial research mainly focused on the production of embryos and birth rates.…”
Section: Discussionmentioning
confidence: 99%
“…More than one and a half million bovine embryos were produced in vitro worldwide in 2021 2 , but 60% had to be transferred fresh due to the lack of a reliable cryopreservation method that results in favorable pregnancy rates 2,7,8 . Consequently, a large number of embryo recipient animals must be available, resulting in increased costs 9,10 . Predicting blastocyst yield and optimization of a vitrification protocol would allow to decrease the number of recipients per calf born and to optimize the logistics of the IVEP process.…”
Section: Embryo Morphokinetics Derived From Fresh and Vitrified Bovin...mentioning
confidence: 99%
“…In a recent review, Contreras et al [ 112 ] pointed out several shortcomings associated with applying embryo transfer in small community farmers. The advantage of placing F1 embryos in F1 recipients is that it would eliminate the need for crossbreeding cattle, which is difficult and time-consuming (see the section on Genetics).…”
Section: Breeding Proceduresmentioning
confidence: 99%